Comparison of In Vitro developmental competence of cloned caprine embryos using donor karyoplasts from adult bone marrow mesenchymal stem cells vs ear fibroblast cells - Kwong, P.J.; Nam, H.Y.; Khadijah, W.E.W.; Kamarul, Tunku; Abdullah, R.B. (2014)
Contents The aim of this study was to produce cloned caprine embryos using either caprine bone marrow-derived mesenchymal stem cells (MSCs) or ear fibroblast cells (EFCs) as donor karyoplasts. Caprine MSCs were isolated from male Boer goats of an average age of 1.5years. To determine the pluripotency of MSCs, the cells were induced to differentiate into osteocytes, chondrocytes and adipocytes. Subsequently, MSCs were characterized through cell surface antigen profiles using specific markers, prior to their use as donor karyoplasts for nuclear transfer. No significant difference (p>0.05) in fusion rates was observed between MSCs (87.7) and EFCs (91.3) used as donor karyoplasts. The cleavage rate of cloned embryos derived with MSCs (87.0) was similar (p>0.05) to those cloned using EFCs (84.4). However, the in vitro development of MSCs-derived cloned embryos (25.3) to the blastocyst stage was significantly higher (p<0.05) than those derived with EFCs (20.6). In conclusion, MSCs could be reprogrammed by caprine oocytes, and production of cloned caprine embryos with MSCs improved their in vitro developmental competence, but not in their fusion and cleavage rate as compared to cloning using somatic cells such as EFCs.